Projeto e dimensionamento de sistemas de freios de veículos Baja SAE - Oliveira, Luiz Henrique Fujimoto da Silva de (2022)
The Baja SAE project was created at the University of South Carolina, located in the United States of America, where the first competition was held in 1976. Later, the project started in Brazil, where it became known as Baja SAE Brasil . The Baja SAE Brasil project started its activities in 1994, in which engineering students from several higher education universities have the opportunity to apply the knowledge acquired in the classroom in practice. The participants of the Baja SAE Brasil project prepare a prototype of a off-road vehicle, going through all stages of vehicle manufacture, as well as design, manufacturing and instrumentation. This work focuses on presenting the entire process of developing the brake system for Baja vehicles, especially for the team at the Federal University of São Carlos. Therefore, the design of the brake system was carried out, taking into account several geometric aspects of the vehicle, seeking to achieve comfort, safety and better drivability when braking the vehicle. In addition, we sought a system that is ergonomic for the user, with less effort on his part, and a brake system that has an optimized manufacture and maintenance of some components, such as the drive pedal, caliper attachments and brake discs.